1991
DOI: 10.3171/jns.1991.74.3.0415
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous neuronal hyperactivity in the medial and intralaminar thalamic nuclei of patients with deafferentation pain

Abstract: Electrical activity was recorded from single cells in the thalamus of 10 patients with chronic pain associated with deafferentation. Under local anesthesia, these patients underwent either electrode implantation or thalamotomy for treatment of their pain. In eight of the 10 patients, single units were identified as discharging spontaneously in high-frequency, often rhythmic, bursts. The discharges were of two types: short bursts comprised of two to six spikes with a burst frequency of one to four per second; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(87 citation statements)
references
References 27 publications
1
84
1
1
Order By: Relevance
“…The convulsive pain of injury to the brachial plexus may correlate with the burst pattern of firing. Abnormal bursting patterns after deafferentation are also observed in higher levels of the central nervous system including the thalamus (Rinaldi et al 1991). Transfer of healthy intercostal nerve into trunk nerves of the upper limb may inhibit this abnormal electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The convulsive pain of injury to the brachial plexus may correlate with the burst pattern of firing. Abnormal bursting patterns after deafferentation are also observed in higher levels of the central nervous system including the thalamus (Rinaldi et al 1991). Transfer of healthy intercostal nerve into trunk nerves of the upper limb may inhibit this abnormal electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in the somatosensory thalamus of patients with neuropathic pain display high spontaneous firing rates, abnormal bursting activity, and evoked responses to stimulation of body areas that normally do not activate these neurons (Gorecki et a1. 1989;Hirayama et al 1989;Lenz et al 1989;Rinaldi et al 1991). The site of abnormality in thalamic function appears to be somatotopically related to the painful region.…”
Section: Denercation Hypersensitidty and Neuronal Hyperactivitymentioning
confidence: 99%
“…It is tempting to speculate that perhaps the contribution of It and Ih conductances to Pf cell physiology may change in certain disease states. Several studies have reported changes in the firing properties of Pf cells after deafferentation, such as the loss of intrathalamic and ascending sensory projections (Rinaldi et al, 1991;Pollin et al, 1997;Vaculin et al, 2000). It would be interesting if there were increases in both the expression and/or efficacy of It and Ih channels in Pf cells after deafferentation, or in certain disease pathologies or aberrant developmental paradigms, such that a switch occurs in the electrophysiological properties of these cells results in the expression of a more classic oscillatory thalamic neuron physiology.…”
Section: Functional Significancementioning
confidence: 99%